Identification of both GABAA receptors and voltage-activated Na+ channels as molecular targets of anticonvulsant α-asarone - Wang, Ze-Jun; Levinson, Simmon R.; Sun, Liqin; Heinbockel, Thomas (Frontiers in Pharmacology, 2014)
Alpha (α)-asarone, a major effective component isolated from the Chinese medicinal herb Acorus tatarinowii, is clinically used as medication for treating epilepsy, cough, bronchitis, and asthma. In the present study, we demonstrated that α-asarone targets central nervous system GABAA receptor as well as voltage-gated Na+ channels. Using whole-cell patch-clamp recording, -asarone inhibited spontaneous firing of output neurons, mitral cells (MCs), in mouse olfactory bulb brain slice preparations and hyperpolarized the membrane potential of MCs. The inhibitory effect of α-asarone persisted in the presence of ionotropic glutamate receptor blockers but was eliminated after adding a GABAA receptor blocker, suggesting that GABAA receptors mediated the inhibition of MCs by α-asarone. This hypothesis was supported by the finding that α-asarone evoked an outward current, but did not influence inhibitory postsynaptic currents (IPSCs). In addition to inhibiting spontaneous firing, α-asarone also inhibited the Nav1.2 channel, a dominant rat brain Na+ channel subtype. The effects of α-asarone on a defined Nav1.2 were characterized using transfected cells that stably expressed the Nav1.2 channel isoform. α-Asarone displayed strong tonic inhibition of Nav1.2 currents in a concentration- and membrane potential-dependent fashion. α-Asarone reduced channel availability in steady-state inactivation protocols by enhancing or stabilizing Na+ channel inactivation. Both Na+ channel blockade and activation of GABAA receptors provide a possible mechanism for the known anti-epileptic effects of α-asarone. It also suggests that α-asarone could benefit patients with cough possibly through inhibiting a Na+ channel subtype to inhibit peripheral and/or central sensitization of cough reflexes.